1999
DOI: 10.1038/sj.mp.4000543
|View full text |Cite
|
Sign up to set email alerts
|

Genetic alteration of the α2-adrenoceptor subtype c in mice affects the development of behavioral despair and stress-induced increases in plasma corticosterone levels

Abstract: ␣ 2 -Adrenoceptors (␣ 2 -AR) modulate many central nervous system functions, such as regulation of sympathetic tone, vigilance, attention, and reactivity to environmental stressors. Three ␣ 2 -AR subtypes (␣ 2A , ␣ 2B , and ␣ 2C ) with distinct tissue-distribution patterns are known to exist, but the functional significance of each subtype is not clear. Since specific, ␣ 2 -AR subtype-selective pharmacological probes are not available, mice with genetically altered ␣ 2C -AR expression were studied in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
69
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(75 citation statements)
references
References 42 publications
3
69
0
3
Order By: Relevance
“…The ␣ 2C -adrenoreceptors are primarily expressed in the central nervous system and recent studies of ␣ 2C adrenoreceptor knockout mice demonstrate this receptor subtype plays a role in modulating several aspects of behavior (5,14,15) and in regulating catecholamine release from sympathetic neurons in the heart (16,17). Our results provide evidence for cell-type specific targeting of G protein-coupled receptors and for the development of receptor microdomains during neuronal differentiation of PC12 cells.…”
supporting
confidence: 48%
See 1 more Smart Citation
“…The ␣ 2C -adrenoreceptors are primarily expressed in the central nervous system and recent studies of ␣ 2C adrenoreceptor knockout mice demonstrate this receptor subtype plays a role in modulating several aspects of behavior (5,14,15) and in regulating catecholamine release from sympathetic neurons in the heart (16,17). Our results provide evidence for cell-type specific targeting of G protein-coupled receptors and for the development of receptor microdomains during neuronal differentiation of PC12 cells.…”
supporting
confidence: 48%
“…The tissue distribution of ␣ 2C -adrenoreceptors is primarily confined to the central nervous system (21,22). Recent evidence from transgenic and knockout mouse models show that the ␣ 2C -adrenoreceptors modulate several aspects of behavior (5,14,15). Both ␣ 2A and ␣ 2C receptors have been shown to regulate catecholamine release from sympathetic nerve terminals (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, ␣ 2C AR knockout mice performed less accurately in a delayed alternation task and displayed slowed motor initiation in the return phase of the task, supporting a role for the ␣ 2C AR in the cognitive aspect of response preparation. ␣ 2C AR knockout mice were also impaired in spatial and nonspatial water maze tests, thus supporting a role for this receptor in modulating cognitive functions (5), and alteration of ␣ 2C AR expression in transgenic mice has also been linked with behavioral despair development and changes in plasma corticosterone levels (11). Recent studies measuring [ 3 H]norepinephrine release from central neurons and cardiac sympathetic nerves have shown that the frequency-release curves for ␣ 2C AR-deficient mice are rightward shifted compared with wild-type mice (9).…”
Section: Resultsmentioning
confidence: 99%
“…␣ 2 AR are widely expressed within the central and peripheral nervous system (2-4) and participate in a broad spectrum of physiologic functions such as regulation of blood pressure both centrally and within the vasculature, sedation, analgesia, regulation of insulin release, renal function, and cognitive and behavioral functions (5)(6)(7)(8)(9)(10)(11)(12). Three human ␣ 2 AR subtypes have been cloned and characterized (␣ 2A , ␣ 2B , and ␣ 2C ).…”
mentioning
confidence: 99%